Physicochemical and sensory analysis of instant corn porridge made from nixtamalized waxy corn [Analisis sifat fisikokimia dan sensoris bubur jagung instan berbahan dasar jagung pulut nikstamal] - Nunu, Nirmawaty; Ahmad, Lisna; Liputo, Siti Aisa (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Waxy corn is a commodity that can be developed into various food products; one is instant porridge, which only requires a short cooking preparation process because it has undergone previous processing. This research aimed to determine the physicochemical and sensory properties of instant porridge made from nixtamalized waxy corn. This research used a completely randomized factorial design (CRFD). The first factor was soaking time (30, 60, and 90 minutes), and the second was pregelatinization time (5, 10, and 15 minutes). The results showed that soaking and pregelatinization time significantly affected rehydration capacity, rehydration time, and viscosity. In contrast, the effect on syneresis and sensory properties was only affected by one of the factors. Instant nixtamalized corn porridge with a soaking time of 90 minutes and a pregelatinization time of 15 minutes was the best instant nixtamalized corn porridge with highest rehydration capacity (5.78 ml/g), calcium content (66.80 mg/L), and viscosity (3850 cP), smallest syneresis value (29.94%), and shortest rehydration time (2.19 minutes), with a neutral taste preference, while the panelists somewhat preferred color, texture, and aroma.